2016
DOI: 10.1590/0074-02760160085
|View full text |Cite
|
Sign up to set email alerts
|

Zika virus damages the human placental barrier and presents marked fetal neurotropism

Abstract: An unusually high incidence of microcephaly in newborns has recently been observed in Brazil. There is a temporal association between the increase in cases of microcephaly and the Zika virus (ZIKV) epidemic. Viral RNA has been detected in amniotic fluid samples, placental tissues and newborn and fetal brain tissues. However, much remains to be determined concerning the association between ZIKV infection and fetal malformations. In this study, we provide evidence of the transplacental transmission of ZIKV throu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
238
0
7

Year Published

2016
2016
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 235 publications
(253 citation statements)
references
References 26 publications
8
238
0
7
Order By: Relevance
“…ZIKV has been detected in amniotic fluid, placental tissues, and fetal and newborn brains (Calvet et al, 2016;Driggers et al, 2016;Mlakar et al, 2016;Noronha et al, 2016), suggesting that ZIKV can cross the placenta and infect fetal brains. Furthermore, it has been reported that ZIKV can infect human placental macrophages and trophoblasts (Quicke et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…ZIKV has been detected in amniotic fluid, placental tissues, and fetal and newborn brains (Calvet et al, 2016;Driggers et al, 2016;Mlakar et al, 2016;Noronha et al, 2016), suggesting that ZIKV can cross the placenta and infect fetal brains. Furthermore, it has been reported that ZIKV can infect human placental macrophages and trophoblasts (Quicke et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…The role of pathology should not be underestimated in coming to the conclusion that Zika virus causes fetal malformations. 22 The initial reports in February 2016 of the fetal pathology occurring in fetuses and neonates with intrauterine Zika virus infection and microcephaly and with destructive brain lesions and Zika virus infection, 9,10 together with pathology and autopsy findings in subsequent cases, [12][13][14] were important factors in determining the causal role of this virus in producing fetal malformations. A variety of ophthalmic changes have been identified in neonates with congenital microcephaly and Zika virus infection, 23 but none of the reported autopsies have included pathologic examination of the eyes to study these ocular abnormalities in detail.…”
Section: Discussionmentioning
confidence: 99%
“…In February 2016, the World Health Organization declared ZIKV infection a public health emergency, issuing a global alert about its relationship to cases of microcephaly, considering that the viral genome was found in blood samples and tissues of microcephalic neonates 27 . Moreover, amniotic fluid analysis of microcephalic fetuses from pregnant women found ZIKV infection, inferring transplacental transmission 5,28 . This fact could explain the increased number of microcephaly cases reported in Brazil.…”
Section: Warning Of Neurological Complications Of Dengue Zika and Cmentioning
confidence: 99%